Diurnal changes in blood metabolite and hormone concentrations according to milking and feeding times in Holstein cows in pasture-based systems - M. C. Prieto; J. P. Damián; A. Félix; A. Meikle; V. de Brun (Tropical Animal Health and Production, 2026)

Calibration of visible and near-infrared spectral imaging technology to predict the quality evolution of retail fresh pork bellies with different fat content - Michela Albano-Gaglio; Carlos A. Esquerre; Colm P. O’Donnell; Israel Muñoz; Gamal ElMasry; Maria Font-i-Furnols; Juan F. Tejeda; Albert Brun; Elsa Lloret; Begonya Marcos (Food Research International, 2025)

High temperatures reduce growth, infection, and transmission of a naturally occurring fungal plant pathogen - Dalia V. Chen; Samuel P. Slowinski; Allyson K. Kido; Emily L. Bruns (Ecology, 2024)
Climate change is rapidly altering the distribution of suitable habitats for many species as well as their pathogenic microbes. For many pathogens, including vector‐borne diseases of humans and agricultural pathogens, climate change is expected to increase transmission and lead to pathogen range expansions. However, if pathogens have a lower heat tolerance than their host, increased warming could generate so‐called thermal refugia for hosts. Predicting the outcomes of warming on disease transmission requires detailed knowledge of the thermal tolerances of both the host and the pathogen. Such thermal tolerance studies are generally lacking for fungal pathogens of wild plant populations, despite the fact that plants form the base of all terrestrial communities. Here, we quantified three aspects of the thermal tolerance (growth, infection, and propagule production) of the naturally occurring fungal pathogen Microbotryum lychnidis‐dioicae , which causes a sterilizing anther‐smut disease on the herbaceous plant Silene latifolia . We also quantified two aspects of host thermal tolerance: seedling survival and flowering rate. We found that temperatures >30°C reduced the ability of anther‐smut spores to germinate, grow, and conjugate in vitro. In addition, we found that high temperatures (30°C) during or shortly after the time of inoculation strongly reduced the likelihood of infection in seedlings. Finally, we found that high summer temperatures in the field temporarily cured infected plants, likely reducing transmission. Notably, high temperatures did not reduce survival or flowering of the host plants. Taken together, our results show that the fungus is considerably more sensitive to high temperatures than its host plant. A warming climate could therefore result in reduced disease spread or even local pathogen extirpation, leading to thermal refugia for the host.

Diversity and seasonal variation of the molluscan community associated with the seagrass Halodule wrightii in a marine protected area in the southern Gulf of California - C. J. Pérez-Estrada; R. Rodríguez-Estrella; F. G. Brun-Murillo; P. Gurgo-Salice; R. Valles-Jiménez; E. Morales-Bojórquez; M. A. Medina-López (Aquatic Ecology, 2023)

A microfluidic device for extracellular vesicle purification: an in-vitro study on mammary gland tumours - V. Moccia; A. Meggiolaro; P. Brun; A. Sammarco; D. Ferraro; V. Zappulli (Journal of Comparative Pathology, 2023)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity - L. M. Soissons; M. M. van Katwijk; G. Peralta; F. G. Brun; P. G. Cardoso; T. F. Grilo; B. Ondiviela; M. Recio; M. Valle; J. M. Garmendia; F. Ganthy; I. Auby; et al. (Limnology and Oceanography, 2018)
Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.

Pollen limitation may be a common Allee effect in marine hydrophilous plants: implications for decline and recovery in seagrasses - B. I. Van Tussenbroek; L. M. Soissons; T. J. Bouma; R. Asmus; I. Auby; F. G. Brun; P. G. Cardoso; N. Desroy; J. Fournier; F. Ganthy; J. M. Garmendia; L. Godet; et al. (Oecologia, 2016)

Defining the structural characteristics of annexin V binding to a mimetic apoptotic membrane - Jingxiong Lu; Anton P. Le Brun; Seong Hoong Chow; Takuya Shiota; Bo Wang; Tsung-Wu Lin; Guei-Sheung Liu; Hsin-Hui Shen (European Biophysics Journal, 2015)

Effect of willow short rotation coppice on soil properties after three years of growth as compared to forest, grassland and arable land uses - M. Stauffer; C. Leyval; J.-J. Brun; P. Leportier; J. Berthelin (Plant and Soil, 2014)

Climate change interactions affect soil carbon dioxide efflux and microbial functioning in a post-harvest forest - M. D. McDaniel; J. P. Kaye; M. W. Kaye; M. A. Bruns (Oecologia, 2014)

Mapping the role of tropical cyclones on the hydroclimate of the southeast United States: 2002–2011 - Julien Brun; Ana P. Barros (International Journal of Climatology, 2014)
The role of tropical cyclones ( TCs ) in the water budget of 3211 watersheds in the southeast United States ( SE US ) over the last decade (2002–2011) is examined in detail at daily and longer time‐scales towards mapping regional hydro‐climatic vulnerabilities. The work documents highly heterogeneous spatial and inter‐annual patterns of variability in the contribution of TC events to the annual cycle of rainfall from below 5% (e.g. 2011) to 65–70% (e.g. 2004 and 2005) at the watershed scale. The data indicate that, with average return periods of 1–3 years, singular TCs are key agents of drought demise redressing watershed precipitation deficits by 30–100%, and a key mechanism of regional meteorological drought mitigation at seasonal and inter‐annual time‐scales. Flood response and drought mitigation impacts of TCs are stronger for storms with terrestrial tracks predominantly on the Atlantic region and, or aligned with the Appalachian Mountains (AM) where orographic effects are evident in high precipitation amounts and high runoff ratios. Locally, rainfall‐runoff response along the terrestrial tracks of TCs increases when inter‐storm arrivals are short ( TCs should have a positive impact on regional water resources by reducing or interrupting and eliminating severe drought, especially in the Piedmont and Coastal Plains, the impact on river discharge should mostly affect the magnitude of the bank‐full and low hydroperiodicity flooding (≤5‐year events) that are tightly linked to the functional resiliency of natural and developed landscapes.

Impact of a program combining pre-authorization requirement and post-prescription review of carbapenems: an interrupted time-series analysis - T. Delory; A. Pontfarcy; A. Emirian; F. About; B. Berdougo; C. Brun-Buisson; P. Lesprit (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

Unsolicited post-prescription antibiotic review in surgical and medical wards: factors associated with counselling and physicians’ compliance - P. Lesprit; C. Landelle; C. Brun-Buisson (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Vegetation activity monitoring as an indicator of eco-hydrological impacts of extreme events in the southeastern USA - Julien Brun; Ana P. Barros (International Journal of Remote Sensing, 2013)

Structural effects of the antimicrobial peptide maculatin 1.1 on supported lipid bilayers - David I. Fernandez; Anton P. Le Brun; Tzong-Hsien Lee; Paramjit Bansal; Marie-Isabel Aguilar; Michael James; Frances Separovic (European Biophysics Journal, 2013)

Assessment of the Environmental Quality of French Continental Mediterranean Lagoons with Oyster Embryo Bioassay - F. Galgani; J. Senia; J. L. Guillou; T. Laugier; D. Munaron; B. Andral; B. Guillaume; E. Coulet; P. Boissery; L. Brun; M. C. Bertrandy (Archives of Environmental Contamination and Toxicology, 2009)

Serpentine and non‐serpentine ecotypes of Collinsia sparsiflora associate with distinct arbuscular mycorrhizal fungal assemblages - S. P. SCHECHTER; T. D. BRUNS (Molecular Ecology, 2008)
Although plant adaptation to serpentine soils has been studied for several decades, the mechanisms of plant adaptation to edaphic extremes are still poorly understood. Arbuscular mycorrhizal fungi (AMF) are common root symbionts that can increase the plant hosts’ establishment and growth in stressful environments. However, little is known about the role plant–AMF interactions play in plant adaptation to serpentine. As a first step towards understanding this role, we examined the AMF assemblages associated with field populations of serpentine and non‐serpentine ecotypes of California native plant Collinsia sparsiflora . We sampled roots of C. sparsiflora from three serpentine and three non‐serpentine sites in close proximity (110 m to 1.94 km between sites) and analysed the small subunit ribosomal DNA gene amplified from root DNA extracts using AMF‐specific primers. A total of 1952 clones from 24 root samples (four from each site) were sequenced. We used sequence similarity and phylogenetic analysis to determine operational taxonomic units (OTU) resulting in 19 OTUs representing taxa from six AMF genera, including one serpentine‐specific OTU. We used Bray–Curtis similarity, multidimensional scaling and analysis of similarity to compare root sample AMF assemblages. These analyses clearly showed that plant ecotypes associated with distinct AMF assemblages; an Acaulospora OTU‐dominated serpentine, and a Glomus OTU‐dominated non‐serpentine assemblages. Species diversity and evenness were significantly higher in serpentine assemblages. Finally, relate analysis showed a relationship between ecotype AMF assemblages and soil nutrients. This study reveals a strong relationship between AMF associates and plant adaptation to edaphic extremes.

Interaction between hydrodynamics and seagrass canopy structure: Spatially explicit effects on ammonium uptake rates - E. P. Morris; G. Peralta; F. G. Brun; L. van Duren; T. J. Bouma; J. L. Perez-Llorens (Limnology and Oceanography, 2008)
The hypotheses that (1) different seagrass morphologies may facilitate different nutrient uptake rates under similar hydrodynamic forcing and (2) this effect on nutrient uptake rates is spatially explicit, with the highest uptake rates at edges of patches, where currents and turbulence are highest, were examined under unidirectional flow conditions. Homogeneous patches (2 m long) of two seagrass species ( Cymodocea nodosa and Zostera noltii ) with contrasting shoot size and density were placed in a race track flume. 15 NH 4 + uptake and hydrodynamic properties along a gradient from outside to inside the patch were measured at a range of current velocities (0.05 to 0.3 m s ‐1 ). For each velocity we also determined the height and bending of the canopy. Water velocity affected the ammonium uptake rate of both species. The almost double uptake rates of C. nodosa shoots, compared to those of Z. noltii , were mainly attributed to a twofold difference in the within‐canopy water flow ( Q c , m 3 s ‐1 ). Spatial patterns in canopy water flow were highly correlated with spatial patterns in NH 4 + uptake, thereby explaining the 20% higher uptake rates at the leading edge of both canopies. The correlation between spatial patterns in canopy water flow and ammonium uptake rates underlines the role of canopy and patch configuration in determining the functioning of seagrass landscapes and their associated ecosystem services, such as nitrogen assimilation.

Monitoring the assembly of antibody-binding membrane protein arrays using polarised neutron reflection - Anton P. Le Brun; Stephen A. Holt; Deepan S. Shah; Charles F. Majkrzak; Jeremy H. Lakey (European Biophysics Journal, 2008)

Campylobacter fetus bloodstream infection: risk factors and clinical features - L. Gazaigne; P. Legrand; B. Renaud; B. Bourra; E. Taillandier; C. Brun-Buisson; P. Lesprit (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Detection, introgression and localization of genes conferring specific resistance to Leptosphaeria maculans from Brassica rapa into B. napus - M. Leflon; H. Brun; F. Eber; R. Delourme; M. O. Lucas; P. Vallée; M. Ermel; M. H. Balesdent; A. M. Chèvre (Theoretical and Applied Genetics, 2007)

Impact of carbonaceous aerosol emissions on regional climate change - E. Roeckner; P. Stier; J. Feichter; S. Kloster; M. Esch; I. Fischer-Bruns (Climate Dynamics, 2006)

Major Gene and Polygenic Resistance to Leptosphaeria maculans in Oilseed Rape (Brassica napus) - R. Delourme; A. M. Chèvre; H. Brun; T. Rouxel; M. H. Balesdent; J. S. Dias; P. Salisbury; M. Renard; S. R. Rimmer (European Journal of Plant Pathology, 2006)

A Method to Quantify and Analyze the Foraging Activity of Honey Bees: Relevance to the Sublethal Effects Induced by Systemic Insecticides - M. E. Colin; J. M. Bonmatin; I. Moineau; C. Gaimon; S. Brun; J. P. Vermandere (Archives of Environmental Contamination and Toxicology, 2004)

Holocene and modern sediments in the Seine estuary (France): a synthesis - P. Lesueur; S. Lesourd; D. Lefebvre; S. Garnaud; J. C. Brun‐Cottan (Journal of Quaternary Science, 2003)
This synthesis of numerous studies on the Holocene and modern sediments in the macrotidal setting of the Seine estuary demonstrates their overall evolution. In common with a number of estuaries, the lower Seine was an incised valley during the Weichselian glacio‐eustatic sea‐level fall, and infilling occurred during the subsequent lowstand, the Holocene sea‐level rise and the late Holocene stillstand. In the upper estuary, above the basal gravel bed, fluvial freshwater deposits filled the valley. Next, fine sand and silts invaded the estuary upstream to Rouen; the sequence ends in loam, resulting from an increase in the supply of sediment to the fluvial system. In the upper estuary, anthropogenic deepening of the modern channel results in erosion of the Holocene sediments; the only bedforms are thin and narrow sand sheets and some rare megaripples. In the lower estuary, above the Weichselian basal gravel, the Holocene wedge records the change from a transgressed fluvial setting (i.e. gravel beds) to an open estuarine environment (i.e. tidal delta). The modern Seine estuary has been progressively infilled by marine sands and silts. Now silts and clays supplied during high river flows accumulate at the outlet, and offshore sands and gravel of the eastern Bay of the Seine are temporarily covered with veneers of mud. These freshly deposited muds (i.e. mud patches) are periodically partly reworked by waves and strong tidal currents, but silting of the inner shelf is noticeable. Copyright © 2003 John Wiley & Sons, Ltd.

Molecular Dynamics of Biological Probes by Fluorescence Correlation Microscopy with Two-Photon Excitation - E. Guiot; M. Enescu; B. Arrio; G. Johannin; G. Roger; S. Tosti; F. Tfibel; F. Mérola; A. Brun; P. Georges; M. P. Fontaine-Aupart (Journal of Fluorescence, 2000)

Study of implanted biomaterial functionality by diphosphonate molecules labeled with radioactive99mTc - J. L. Irigaray; H. Oudadesse; V. Brun; P. Labarre; M. Rapp; J. C. Madelmont; J. Bonafous (Biological Trace Element Research, 1999)

Raynaud's phenomenon and acral necrosis after chemotherapy for AIDS-related Kaposi's sarcoma - M. Reiser; C. Bruns; P. Hartmann; B. Salzberger; V. Diehl; G. Fätkenheuer (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Selection of stable Brassica napus-B. juncea recombinant lines resistant to blackleg (Leptosphaeria maculans). 1. Identification of molecular markers, chromosomal and genomic origin of the introgression - A. M. Chèvre; P. Barret; F. Eber; P. Dupuy; H. Brun; X. Tanguy; M. Renard (Theoretical and Applied Genetics, 1997)

Food availability and growth of the brook trout, Salvelinus fontinalis (Mitchill), in a French Alpine lake - L. CAVALLI; R. CHAPPAZ; P. BOUCHARD; G. BRUN (Fisheries Management and Ecology, 1997)
Plan Vianney lake, situated in the Oisans massif (French Alps) at an altitude of 2250 m, has a fish fauna composed of brook trout, Salvelinus fontinalis (Mitchell), and Artic charr, Salvelinus alpinus (L.). The present study examines the feeding behaviour of S. fontinalis in 1993–94 but also gives some data on S. alpinus . The brook trout represented 80% of the fish fauna of the lake. Dietary analysis showed that this species is an opportunistic feeder and revealed similarities in the trophic niches of S. fontinalis and S. alpinus and a low level of potentially available food resources. The annual growth of S. fontinalis was short and the growth rate was slow compared with other populations. Under these extreme conditions, female fish required several summers to replenish their reserves of energy and were only in condition to spawn once every 2 or 3 years. Although the fecundity of the population was low, it was sufficient to maintain the species in the lake which is not exploited.

Results of the fifth joint pesticide testing programme carried out by the IOBC/WPRS-Working Group “Pesticides and beneficial organisms” - S. A. Hassan; F. Bigler; H. Bogenschütz; E. Boller; J. Brun; J. N. M. Calis; P. Chiverton; J. Coremans-Pelseneer; C. Duso; G. B. Lewis; F. Mansour; L. Moreth; et al. (BioControl, 1991)

Acclimatation sur la côte d'azur et en corse deSerangium parcesetosum [Col.: Coccinellidae] prédateur de l'aleurode des citrus,Dialeurodes citri [Hom.: Aleyrodidae] - J. C. Malausa; E. Franco; P. Brun (BioControl, 1988)

Aquatic vegetation of Lake Annecy - J. P. Dubois; G. Blake; P. Gerbeaux; G. Brun (Aquatic Sciences, 1988)

Human lysosomal genes: Arylsulfatase A and ?-Galactosidase - G. A. P. Bruns; B. J. Mintz; A. C. Leary; V. M. Regina; P. S. Gerald (Biochemical Genetics, 1979)

Adenylate kinase 2, a mitochondrial enzyme - Gail A. P. Bruns; Violet M. Regina (Biochemical Genetics, 1977)

Expression of ?-d-mannosidase in man-hamster somatic cell hybrids - Peter H. Ingram; Gail A. P. Bruns; Violet M. Regina; Robert E. Eisenman; Park S. Gerald (Biochemical Genetics, 1977)

Some aspects of metabolic activation of chemical carcinogens in relation to their organ specificity - H. Bartsch; G. P. Margison; C. Malaveille; A. M. Camus; G. Brun; J. M. Margison; G. F. Kolar; M. Wiessler (Archives of Toxicology, 1977)

Expression of the human adenylate kinase isozymes, phosphopyruvate hydratase, 6-phosphogluconate dehydrogenase, and phosphoglucomutase-1 in man-rodent somatic cell hybrids - Gail A. P. Bruns; Park S. Gerald (Biochemical Genetics, 1976)